Dialectics of existential space in educational societies - Makhamatov, Tair; Ganiyev, Bahodirjon; Pulatova, Dildor Akmalovna; Makhamatov, Timour (XLinguae, 2024)
This article presents a philosophic analysis of existentiality of the space of society. The authors base their research on an analysis of the works of J.-P. Sartre, A. Camus, K. Jaspers, C. Jung, L, Vygotsky, E. Fromm, J. Salinger, S. Beckett, and other recent representatives of existential philosophy, psychology, and existential fiction. The main goal of the present study is to define the existential space and discuss the main determinants of existentialization of social ontology. The results of this study are as follows: definition of the existential social space as a space of society where negative socio-psychological tensions, dominance of “the war of all against all”, and indifference of the society towards its members engender and intensify the existential tension in its representatives; discussion of a special feature of the social time existence, which is formed under the influence of space existence and manifested as slowing down, stopping, or acceleration of time in the perception of an existential subject; description of the main levels of the existential space and time of society; suggestion of possible methods of dialectical “relief” mitigating the existence of the society and its actors.